PCSK9 inhibitor in acute ischemic stroke patient receiving mechanical thrombectomy: early outcomes and safety - Kim, Jonguk; Hong, Uichan; Yoon, Cindy W.; Bae, Jin Woo; Rha, Joung-Ho; Park, Hee-Kwon (Frontiers in Neurology, 2024)
Background Lipid-lowering therapies are mainstays in reducing recurrence after acute ischemic stroke (AIS). Evolocumab, a Proprotein convertase subtilisin-kexin type 9 (PCSK9) inhibitor, is a promising lipid-lowering agent known to decrease LDL cholesterol and mitigate vascular events alongside statins. However, its effects on the early functional outcomes post-mechanical thrombectomy (MT) remain unclear. This study aimed to assess the short-term effects and incidence of bleeding events after the early, off-label use of PCSK9 inhibitors in AIS patients undergoing MT. Methods We retrospectively analyzed patients who had MT at a Regional Stroke Center from December 2018 to April 2023. Our primary outcome was discharge functional outcomes. Secondary outcomes included early neurologic deterioration (END), symptomatic intracerebral hemorrhage (sICH), 3-month functional outcomes, 3-month recurrence rate, and lipid profiles. Results Of 261 patients (mean age 69.2 ± 11.7, men 42.9%), 42 were administered evolocumab peri-procedurally. While baseline characteristics were similar between the two groups, evolocumab group demonstrated improved discharge outcomes, with a lower mean NIHSS (8.8 ± 6.8 vs. 12.4 ± 9.8, p = 0.02) and a higher percentage of patients with discharge mRS ≤ 3 (52.4% vs. 35.6%, p = 0.041). The 3-month follow-up show a non-significant trend toward an improved outcome in the evolocumab group. Multivariable analysis indicated that evolocumab had a potential impact on favorable discharge outcomes (aOR 1.98[0.94–4.22] for mRS ≤ 3 and 0.47[0.27–0.84] for lower ordinal mRS). Notably, evolocuamb users exhibited fewer instances of END and sICH, although they do not reach statistical significance. Additionally, the evolocumab group demonstrated potential benefits in LDL cholesterol reduction over time. Conclusion Early use of evolocumab in AIS patients undergoing MT appeared to be safe and associated with better early functional outcomes. The potential benefit of the PCSK9 inhibitor shown here warrants further prospective studies.